English Teaching Speaking Strategies Applied by Teachers at Junior High School in Karawang - Siregar, Hastrid Hofifah; Srisudarso, Mansyur; Wahyuna, Yuna Tresna (IAI Nasional Laa Roiba Bogor, 2025)
This study provides a qualitative method to examine speaking instruction tactics used by English teachers. The purpose of this study is to look into the methods used by instructors in one of Karawang's junior high schools to teach English-speaking classes. This study also investigates the challenges experienced by English teachers when putting spoken instruction methodologies into practice. In the current study, a narrative analysis research design and a qualitative technique were used. Data was gathered through interviewing and observation. The results demonstrated how these tactics work together and demonstrate how they adhere to the tenets of modern language instruction. These tactics exhibit a communicative and learner-focused methodology. Furthermore, the challenges that educators encounter underscore the significance of establishing a communicative and encouraging atmosphere while instructing speaking, employing an array of techniques, and surmounting students' psychological obstacles to facilitate efficacious language acquisition. Students' speaking abilities and self-confidence are greatly aided by the teacher's facilitation and modelling of language.